2022
DOI: 10.56763/ijfes.v1i.37
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Psychological Capital between Academic Stress and Positive Academic Behaviour of College Students

Abstract: The study was carried out to examine the mediation of psychological capital between academic stress and academic behaviour of college students. Psychological capital included hope, efficacy, resilience, and optimism. Academic stress included frustration,pressure, conflict and anxiety. Positive academic behaviour included academic engagement, perceived academic competence, learning strategies and class room interaction. Participants were 180 randomly selected college students who responded to Luthan’sPsyCap Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In summary, the reviewed research provides insightful information about the complex relationship between pressure, psychological capital, and general well-being in college students. The findings underscore the significance of psychological resources in buffering the negative impact of external pressures and fostering positive outcomes for students [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the reviewed research provides insightful information about the complex relationship between pressure, psychological capital, and general well-being in college students. The findings underscore the significance of psychological resources in buffering the negative impact of external pressures and fostering positive outcomes for students [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although their study did not offer a summary, the selection of a mediator aligns with the overarching theme of comprehending how psychological resources mediate the impact of external pressures on the well-being of college students. Furthermore, Varadwaj and Mahapatra [5] explored the mediation of psychological capital between academic stress and positive academic behavior among college students. The results of their research have demonstrated noteworthy positive associations between the characteristics of psychological capital and positive academic behaviors Furthermore, research has demonstrated that psychological capital functions as a moderator to mitigate the negative effects of academic stress on constructive academic activities.…”
Section: Introductionmentioning
confidence: 99%